(untitled) (TAMADDUN NURI JURNALI, 2024)
The article analyzed the opinions about the presence of lexemes expressing color in Turkish languages. Colors in the culture of each nation have their own symbolic meaning, that is, colors are an expressive factor of the nation’s culture.